Diagnosis and treatment of chlamydia and gonorrhoea in general practice in England 2000–2011: a population-based study using data from the UK Clinical Practice Research Datalink - Wetten, Sally (BMJ Open, 2015)
OBJECTIVES: To determine the relative contribution of general practices (GPs) to the diagnosis of chlamydia and gonorrhoea in England and whether treatment complied with national guidelines. DESIGN: Analysis of longitudinal electronic health records in the Clinical Practice Research Datalink (CPRD) and national sexually transmitted infection (STI) surveillance databases, England, 2000–2011. SETTING: GPs, and community and specialist STI services. PARTICIPANTS: Patients diagnosed with chlamydia (n=1 386 169) and gonorrhoea (n=232 720) at CPRD GPs, and community and specialist STI Services from 2000–2011. MAIN OUTCOME MEASURES: Numbers and rates of chlamydia and gonorrhoea diagnoses; percentages of patients diagnosed by GPs relative to other services; percentage of GP patients treated and antimicrobials used; percentage of GP patients referred. RESULTS: The diagnosis rate (95% CI) per 100 000 population of chlamydia in GP increased from 22.8 (22.4–23.2) in 2000 to 29.3 (28.8–29.7) in 2011 (p<0.001), while the proportion treated increased from 59.5% to 78.4% (p=0.001). Over 90% were prescribed a recommended antimicrobial. Over the same period, the diagnosis rate (95% CI) per 100 000 population of gonorrhoea in GP ranged between 3.2 (3–3.3) and 2.4 (2.2–2.5; p=0.607), and the proportion treated ranged between 32.7% and 53.6% (p=0.262). Despite being discontinued as a recommended therapy for gonorrhoea in 2005, ciprofloxacin accounted for 42% of prescriptions in 2007 and 20% in 2011. Over the study period, GPs diagnosed between 9% and 16% of chlamydia cases and between 6% and 9% of gonorrhoea cases in England. CONCLUSIONS: GP makes an important contribution to the diagnosis and treatment of bacterial STIs in England. While most patients diagnosed with chlamydia were managed appropriately, many of those treated for gonorrhoea received antimicrobials no longer recommended for use. Given the global threat of antimicrobial resistance, GPs should remain abreast of national treatment guidelines and alert to treatment failure in their patients.